Hypoglycemic Seizures and Cognitive Function - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The effect of hypoglycemic seizures on cognitive function was evaluated in 16 children treated for insulin-dependent diabetes mellitus at the Hospital for Sick Children, Toronto, Canada.